Notary's Responsibility For Deeds That Are Not Read, Position Of The Deed And Sanctions For Notaries Who Do Not Read The Deed They Have Made - Pranoto, Mulyo (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This research aims to find out and analyze, that the Notary profession has obligations that should be carried out, to provide legal certainty and ensure that what is contained in the notarial deed can really be understood and is in accordance with what the parties want, the Notary's obligation to read the deed made and explaining the situation of the parties if the deed is not read in front of the parties at the closing of the deed in accordance with the Law. That if there is a misunderstanding between the parties regarding the deed that has been made and this causes the deed to be unclear, then the position of the notarial deed is worthy of being questioned as well as the responsibility of the Notary who deliberately does not read the deed he has made in front of the parties. The method used is the method normative juridical research with a case approach, analytical approach, and legislative approach. The research results showed that reading a deed is an obligation, as one of the bases for an authentic deed made by a Notary, which if not carried out could result in a default on the deed. A notary who deliberately does not read a deed made in front of the parties is a violation which results in the deed he made becoming null and void and its evidentiary power being degraded to a private deed.